2018
DOI: 10.5125/jkaoms.2018.44.6.275
|View full text |Cite
|
Sign up to set email alerts
|

A working paradigm for managing mandibular fractures under regional anesthesia

Abstract: ObjectivesIsolated mandibular fractures contribute to approximately 45% of maxillofacial traumas. Improper management of mandibular fractures can cause myriad potential complications and can lead to serious functional and aesthetic sequelae. The objective of the study is to design a stepwise approach for managing isolated mandibular fractures using open reduction and internal fixation (ORIF) with regional anesthesia on outpatient basis.Materials and MethodsPatients with isolated mandibular fractures presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…According to the literature, regional anaesthesia has many advantages over GA, including elimination of GA-related complications such as atelectasis, pulmonary oedema, nausea and vomiting; less need for postoperative nursing care; shorter recovery time; better postoperative pain relief; and reduced treatment cost. 5,10,12 In accordance with previous research, we present the successful management of bilateral atrophic mandible fractures under local anaesthesia in an elder with significant comorbid medical conditions that precluded the administration of GA.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…According to the literature, regional anaesthesia has many advantages over GA, including elimination of GA-related complications such as atelectasis, pulmonary oedema, nausea and vomiting; less need for postoperative nursing care; shorter recovery time; better postoperative pain relief; and reduced treatment cost. 5,10,12 In accordance with previous research, we present the successful management of bilateral atrophic mandible fractures under local anaesthesia in an elder with significant comorbid medical conditions that precluded the administration of GA.…”
Section: Discussionsupporting
confidence: 78%
“…In 2015, El‐Anwar et al 12 compared the treatment outcomes of parasymphyseal mandibular fractures under regional and GA and concluded that regional anaesthesia could effectively replace GA in selected cases of mandibular fracture, obviating the risks of GA. A more recent study by Chellappa et al 5 involved 23 cases of multiple mandibular fractures, and it was reported that regional anaesthesia was an excellent intraoperative alternative to GA for ORIF of mandibular fractures in selected cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been used in the management of fractures involving both the tooth and nontooth bearing portions of the mandible in well-selected patients. [ 24 25 ] It reduces the need for the operating theatre space (because it can be done in the clinic), admission space, and the duration of hospital stay. This translates to the reduced treatment cost for the patient.…”
Section: Discussionmentioning
confidence: 99%